1994
DOI: 10.1111/j.1439-0310.1994.tb00878.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Colonial Orb‐weaving Spiders during a Solar Eclipse

Abstract: The behavior of colonial orb‐weaving spiders (Metepeira incrassata) in tropical Veracruz, Mexico was studied during the total solar eclipse on July 11, 1991. Spiders behaved in a manner typical of daily activity until totality, when many began taking down webs. After solar reappearance, most spiders that had begun taking down webs rebuilt them. There was no significant difference in the overall activity patterns of spiders during totality across a range of colony sizes. Experimental illumination of part of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…For example, changes in light, air temperature and wind speed are factors of bird behaviour (Burt, 2018). The brief changes in temperature and wind speed are possible sensed by birds and, in combination with reduced light, are interpreted as the beginning of nocturnal changes (Wheeler et al, 1935;Rabin and Doviak, 1989;Uetz et al, 1994 andAnderson, 1999) or large storm, potentially enhancing bird vocalizations as instinctive behaviour (Hartstone-Rose et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, changes in light, air temperature and wind speed are factors of bird behaviour (Burt, 2018). The brief changes in temperature and wind speed are possible sensed by birds and, in combination with reduced light, are interpreted as the beginning of nocturnal changes (Wheeler et al, 1935;Rabin and Doviak, 1989;Uetz et al, 1994 andAnderson, 1999) or large storm, potentially enhancing bird vocalizations as instinctive behaviour (Hartstone-Rose et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Solar eclipses offer a unique opportunity to evaluate the relative influence of unexpected darkness on behaviour of animals due to their sudden interference with local light levels and meteorology (Ritson et al, 2019 andHartstone-Rose et al, 2020). During this event, unusual behaviour of animals has been recorded such as birds ceasing to call (Hughes et al, 2014), birds returning to nocturnal roosts (Wheeler et al, 1935 andJennings et al, 1998), nocturnal insects taking flight (Wheeler et al, 1935 andGreenbank et al, 1980), diurnal fish seeking shelter and nocturnal fishes emerging (Jennings et al, 1998), spiders destroying and deconstructing their webs (Uetz et al, 1994), bats flying down a ravine (Pandey andShukla, 1982 andSanchez et al, 1999), and captive animals altering their activity (Kavanau and Rischer,1973;Mukherjhee, 1984;Branch andGust, 1986 andGil-Burmann, andBeltrami, 2003). These stereotypically nocturnal behaviours during an eclipse may mimic cues relevant to schedules of daily routines (Nilsson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Though occasionally bizarre, modern studies have lent support to the idea that at least some individuals of certain species display altered behavior during these events. In addition to further observations on birds [8,9], the list of investigated species includes insects [10,11,12,13,14], aquatic invertebrates [15,16,17,18,19], primates [20,21,22,23], fish [24,25], rodents [26,27], bats [28,29], and lizards [30,31], as well as larger mammals like blue bull antelope [32] and dairy cattle [33]. However, conclusions vary by study and species.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on animal behavior during solar eclipses have shown mixed responses to solar eclipses. Birds, bees, and spiders seem to behave just as in dusk conditions; returning to roosts, altering foraging behavior, or dismantling webs 5–7 . In contrast, little to no behavioral change was observed in dairy cattle during grazing and in captive chimpanzees 8,9 .…”
Section: Introductionmentioning
confidence: 99%